Fisheries and reproductive biology of Octopus vulgaris (Mollusca: Cephalopoda) in the Gulf of Alicante (Northwestern Mediterranean) - GONZALEZ, M.; BARCALA, E.; PEREZ-GIL, J.L.; CARRASCO, M.N.; GARCIA-MARTINEZ, M.C. (Mediterranean Marine Science, 2011)
The common octopus Octopus vulgarisCuvier, 1797 is the most fished cephalopod species along the Spanish coasts. Its catches are highly fluctuating due to the short life cycle of the species and to the annual variability of the recruitment pattern, strongly dependent on the environmental conditions affecting the eggs and paralarvae. This study examines the common octopus fishery, the catch composition, and the main features of the reproductive biology of this species in the Gulf of Alicante (Spanish Eastern coast, Western Mediterranean FAO division 37.1.1). The common octopus fishery was studied analysing the monthly landing and effort data by fishing gear from 1994 to 2005. Monthly samplings of the commercial O. vulgarislandings from trawlers and clay pots from January 2004 to December 2005 resulted in the measuring of 1833 specimens to enable analysis of the catch composition, and allowed the biological sampling of 1176 individuals to provide the reproductive parameters of the species in the study area. The length-weight relationship calculated for the species was BW = 0.51 * DML 2.87. The yearly sex ratios (males:females) were 1:1 (trawl, 2004), 1:0.74 (trawl, 2005), and 1:0.88 (clay pots, 2005). The size (dorsal mantle length, DML) at maturity of the species in the study area was 9.67 cm for males and 14.38 cm for females. The gonadosomatic index reached a peak between April and July for males and in July for females. The Fulton condition index was lower in both sexes between June and September, and for males in November-December, whereas for both sexes the values of the digestive gland index were at their maximum between June and December. The energy allocation between somatic and reproductive growth was investigated and the results suggested that the energy spent on reproduction mainly came from feeding, and not from energy stored in the mantle tissues or in the digestive gland